Impact of infrastructure on agricultural productivity, export and food security in Pakistan - Tabasam, Nazia (2019)
This macro level study uses a multi-faceted view of infrastructure and examines the impact of various defined categories of infrastructure on agricultural productivity, exports and food security in Pakistan. Pakistan - an agrarian country- lacks infrastructure facilities that may influence agricultural productivity, trade and food security which are crucial elements for developing the agriculture sector. This study therefore examines the effect of capital intensive, capital extensive and institutional infrastructure on agricultural productivity in Pakistan. Autoregressive Distributed Lag (ARDL) method is used to analyse time series data from 1980 to 2015. Long run positive relationship between capital intensive, capital extensive and institutional infrastructure and agricultural productivity is observed. In capital extensive infrastructure, however, credit has an opposing effect on agricultural productivity. The policy implications suggest developing, connecting roads, irrigation, research and extension, health care services and electricity supply to the agriculture sector. Secondly, this study investigates the role of transport, ICT and energy infrastructure on agricultural exports. To achieve this objective, panel data analysis for 20 countries based on gravity model, uses Fixed Effect or Random Effect model chosen by Hausman Test. Findings indicate that the road, air and port related transportation infrastructures positively affect agricultural exports. Foreign ports in trading countries also have a positive effect. This finding suggests more investment in transportation facilities, specifically ports. Likewise, ICT and energy infrastructure is significant in boosting agricultural exports in Pakistan. Finally, this study identifies the effect of infrastructure for food access and food utilization, on food security. Safe drinking water is found to be significantly positive in enhancing food security, whereas sanitation and health is negatively significant. Results for food access as a variable indicate building road and rail networks reduce food insecurity. This finding suggests policy action should prioritize the supply of safe drinking water to markedly address the issue of food insecurity. In addition to the practical implications identified above, this research reduces the scarcity of literature focusing on the components of infrastructure that are crucial for agriculture-sector development.